Hydrodynamic performance on sloshing process in a liquid oxygen tank under intermittent excitation. (March 2019) - Liu, Zhan; Feng, Yuyang; Lei, Gang; Li, Yanzhong
Highlights: The hydrodynamic performance in a liquid oxygen tank is numerically studied under an intermittent sloshing excitation. Variations of sloshing parameters and interface dynamic fluctuation are greatly predicted. Performance comparison is made between the continuous and intermittent sinusoidal excitations. Abstract: Fluid sloshing in cryogenic fuel storage tanks, is harmful to effective management and safe storage of cryogens, it is necessary to understand the nature of fluid sloshing in depth. In the present study, a numerical model is built to research the hydrodynamic performance in a liquid oxygen tank under an intermittent sloshing excitation. The external heat inputs are considered, and the intermittent excitation is compiled by user-defined functions and implanted into the numerical model. The mesh motion treatment is specially adopted to predict fluctuations of the free surface, coupled with the volume of fluid method. Validated against the sloshing experiments, the present numerical model was proven to have accurate predicting ability on fluid sloshing in cryogenic storage tanks. Based on the developed numerical model, both the sloshing force and moment are monitored. The liquid and vapor phase distributions and pressure distribution are well predicted. Variations of vapor and liquid pressures are analyzed. The dynamic variations of the interfacial monitors are greatly predicted. Finally, the performance comparison between the continuous and intermittent sloshing excitations is made. With some valuable conclusions achieved, the present study could supply some effective references for fluid sloshing suppression under irregular excitations.